MENGATASI STRESS SAAT PANDEMIK DENGAN MEMBUAT BUKU MEWARNAI (Di IEEEL Institute, Tangerang) - Kartini, Aprilia (Jurnal Pengabdian dan Kewirausahaan, 2021)
ABSTRACT                 During the Corona Virus Disease-2019 (Covid-19) pandemic, which has been going on for almost 1 (one) year, many people feel confused, anxious, afraid, and some are also frustrated. This pandemic has an impact on various sectors, such as economy, education, tourism, social and many more. Feelings of fear of contracting and facing death alone and other worries that everyone thinks about so that the level of stress is getting higher. There has been a change in lifestyle that is usually spent with friends now mostly alone at home or boarding house. Those who already have a family have a heavier burden, especially when it comes to dealing with work when working from home or WFH. Coupled with taking care of children's school and household activities. Stress is a person's emotional response caused by external problems or when facing various life problems. To some extent, stress is needed to be prepared to face the threat of problems. This kind of stress is called eustress or normal stress. However, if the stress is prolonged and causes suffering to turn into distress and can cause mental health problems, this should be avoided. One way to deal with stress during a pandemic can be done by making pictures. As stated by Herawati and Iriaji, they argue that drawing is a tool to express thoughts. During a pandemic when people are worried about leaving the house, coloring books are an alternative to relieve stress. But the obstacle is that people are afraid to leave the house to buy books and also during the economic situation in the family that must be regulated because many do not receive full salaries, so making their own coloring books is an alternative.